Myth of Don Juan and Don Juan like a Psycho in the Drama of A.P. Chekhov’s “Fatherlessness” (Proceedings of Southern Federal University. Philology, 2020)
In  A.P.Chekhov’s drama «Fatherlessness» great attention is paid to the myth of Don Juan and its psychotype. The system of characters  in literary context is studied  in gender psychology  aspect as well.  In this  process a violation of gender stereotypes and roles, feminity of male characters and masculinity of  female ones is noted. The author opposes a scientific knowledge  about a woman and a man  with romantism in relations between the sexes in  literature. It is declared that «Fatherlessness» is the first step to a new art antropology: the old socio-moral  principal of typing  gives place to a new  one – individualization. Attempts of characters  to identify themselves with «heroes» in living own life in accordance with literary images  are discredited with  the author’s irony. In the personal existence of the characters, in behavior men and women only their individual features become decisive and meaningful.Key words: A.P.Chekhov, fatherlessness, Don Juan, psychotype, gender, sex, male, female.DOI 10.18522/1995-0640-2020-2-18-26